Hevea genetic transformation for enhanced recombinant pharmaceutical production by the use of hevein promoter - Pappusamy, Arokiaraj; Shuib, Siti Shuhada; Badaruddin, Badrul Ezam; Sunderasan, E. (2010)
Pharmaceuticals produced in the latex cytosol of genetically transformed Hevea can be harvested nondestructively by conventional tapping. This study evaluates the promoter activity of the 5’-untranslated upstream regulating region of hevein gene, which encodes the most abundant soluble protein in Hevea latex. Constructs were prepared with the test hevein promoter fragments Hev P1 (0.35kb), Hev P2 (0.45kb) and Hev P3 (0.73kb) that were inserted 5’ to the pharmaceutical genes i.e. human protamine 1 (HP1) and human atrial natriur tic factor (HANF), in pGPTV-Kan expression vector. The expression vectors containing HP1 and HANF were electroporated into Agrobacterium tumefaciens GV2260 containing supervirulent plasmid pToK47, which were then used to infect Hevea anther callus. The growth of the putative transformed Hevea callus was monitored on kanamycin selection media. The presence of the pharmaceutical genes (HP1 and HANF), the hevein promoter fragments, and nptII selection marker were verified by PCR on sampled putative transformed callus. The remaining callus tissues will be sub-cultured and transferred into differentiation media for embryoids formation and plantlet regeneration.